Determine the relationship of industries related to regional development - Залунина, Ольга Михайловна (Technology audit and production reserves, 2015)
The article describes the structure of the building complex, which includes related industries. It is generated a table of normalized data on key indicators of related industries of building sector industries and are defined ratings for each industry. A prerequisite for economic growth in any country is the increase in the activity of the investment process and innovation. Direct investments in innovation in the real economy are needed. The economic crisis caused the decline in investment, depreciation of fixed assets of enterprises, the decline in industrial production and living standards. Achieving a balance of building in the regions is an extremely difficult task. The problem is that the degree of inter-regional economic cooperation is very controversial and some of material and financial resources generated through the exchange with other areas of the country. Therefore, in the near future indicator of building activity will continue to be the main indicator of regional economic development. Sectoral structure of the building is its division into indicators characterizing the formation of capital investments. The author formed the normalized data table on the main indicators of related industries of building sector and defined ratings for each industry. It is proved that a necessary and important feature of the integrity of the building systems is the unity of resource provision. As the resource unity is meant to ensure of the construction by resources in range and quantities required in the production of finished building products. At the resource unity is provided the closed internal turnover. Resource unity of operation allows the correct approach to the definition of building systems. A necessary condition for an integrated approach is the development of organizational and methodological foundations of the formation of a regional structure of building. For this purpose it is designed production (managing) and control subsystem on the basis of program and target methods. To eliminate the negative trends in construction management it is needed a shift from empirical action to guide the building to science-based integrated design of organizational forms of building, unifying and typification of their elements and the formation and development of rational organizational structures of management on this basis.